Geo-economic evolution in financial and credit policies of Ukraine’s agri-food industry - Chkan, Iryna; Чкан, Ірина Олександрівна; Tulush, Leonid; Vyhovska, Natalia; Svynous, Ivan; Melnik, Maryna (JAKOŚĆ, 2024)
The financial and credit policies of Ukraine's agri-food sector are crucial for its stability and growth, particularly within the changing geo-economic context. Understanding these changes and their impacts is essential for developing effective measures to support the sector.
Keywords: geo-financial systems; financial and credit strategies; agri-food sector; bank financing; funding grants